2012 20th IEEE International Requirements Engineering Conference (RE) 2012
DOI: 10.1109/re.2012.6345838
|View full text |Cite
|
Sign up to set email alerts
|

How do software architects consider non-functional requirements: An exploratory study

Abstract: International audienceDealing with non-functional requirements (NFRs) has posed a challenge onto software engineers for many years. Over the years, many methods and techniques have been proposed to improve their elicitation, documentation, and validation. Knowing more about the state of the practice on these topics may benefit both practitioners' and researchers' daily work. A few empirical studies have been conducted in the past, but none under the perspective of software architects, in spite of the great inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
5
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 29 publications
8
97
5
6
Order By: Relevance
“…not those such as performance etc.) [2]. Overall, this implies a conclusion where, either values are systematically ignored in the practice of NFR elicitation or values may not be NFRs.…”
Section: Non Functional Requirementsmentioning
confidence: 91%
“…not those such as performance etc.) [2]. Overall, this implies a conclusion where, either values are systematically ignored in the practice of NFR elicitation or values may not be NFRs.…”
Section: Non Functional Requirementsmentioning
confidence: 91%
“…As such a conceptual framework that captures the concepts present in the technological context of the system can be used to reason about the decisions after the fact from the source code. Non-functional quality attributes are especially prone to not being documented [14], further strengthening the need for tools to reason about decisions after the fact. Researchers have also found that there is a need to investigate if domain-specific requirements can improve requirements documentation [15].…”
Section: Related Workmentioning
confidence: 99%
“…¿Quién decide los RNF, qué tipos de RNF importan? [27] Perspectiva de los arquitectos y cualidades del software. El conocimiento se intercambia al momento de la obtención de los requisitos [28].…”
Section: Cómo Se Aborda El Conocimiento Fundamentaciónunclassified